Dolnośląska Polityka Wodna. Innowacyjne podejście do integracji polityk sektorowych w kontekście zasobów wodnych .......... 23 - Sieradzka-Stasiak, Aleksandra (Samorząd terytorialny na Dolnym Śląsku: Sprawy, dylematy i wyzwania, 2025)
THE LOWER SILESIAN WATER POLICY: AN INNOVATIVE APPROACH TO INTEGRATING SECTORAL POLICIES IN THE CONTEXT OF WATER RESOURCESThe article emphasises the urgent need to transform water resource management in Lower Silesia in light of multifaceted threats resulting from climate change and unsustainable human activity. The existing fragmented instruments and the insufficient integration of water-related objectives within national policies prompted the regional government of the Lower Silesian Voivodeship to develop and implement the Dolnośląska Polityka Wodna (DPW) [Lower Silesian Water Policy (LSWP)]. The LSWP aims to achieve high water quality and secure water resources for people, ecosystems, and a sustainable economy by 2050 through the integration of water issues into other regional policies and by fostering responsible social attitudes. The key challenges addressed by the LSWP include poor water quality, the adverse effects of extreme weather events, watercourse transformation and landscape drainage, water deficits, ecological disasters, the lack of an integrated knowledge base on water resources, and low levels of public awareness. The policy envisages a range of actions focused on the integration of sectoral policies, strengthening multi-level and inter-institutional cooperation, advocating for more effective water protection, increasing water retention (particularly natural and landscape-based), reducing pollution, protecting and restoring wetlands, river renaturalisation, improved spatial planning, climate change adaptation and mitigation, ensuring water security, and educational initiatives. The LSWP is intended to serve as a strategic framework supporting sustainable water resource management, the protection and restoration of water bodies, and addressing the negative impacts of climate change in Lower Silesia, with a strong emphasis on cross-sectoral integration and public awareness building.